Vitamin D Supplements overdose toxicity-Review - Abbas, Zainab Abdul Kareem; Hameed, Zahraa Ch; Al-Yasiri, Sarah Alwan Malik (Technium BioChemMed, 2025)
Hypervitaminosis D, also known as vitamin D toxicity, is an uncommon but serious condition that occurs when the concentration of vitamin D is much higher than the body needs due to taking large doses of its supplements instead of the diet or even exposure to sunlight. The body regulates the amount of vitamin D entering it as a result of exposure to sunlight. one of serious consequences of vitamin D toxicity is accumulation of calcium in the body, which causes symptoms of nausea, vomiting, weakness, & frequent urination due to (hypercalciuria). These symptoms may develop to extend to bone pain & kidney problems such as calcium stones. This condition is treated by stopping taking the vitamin and reducing foods that contain a lot of calcium, as appropriate treatments are prescribed by the doctor and are given in the form of intravenous fluids & medications such as Corticosteroids or Bisphosphonates. When taking (60,000) IU of vitamin D daily for several months it is considered toxic because this level is much higher than the permissible and recommended limit by Recommended Dietary Allowance (RDA), which is 600 international units of vitamin D daily. In certain cases, higher doses than permitted are used to treating some medical conditions, such as severe vitamin D deficiency, but they must be taken under the supervision of a doctor and at a specific time, while monitoring calcium levels.